The Effectiveness of the Application of Audio Visual Learning Media on Student Learning Outcomes in Class III Natural Science - Juriyah, Rini; Amrullah ZA, Hanif; Aisyah, Nurul (International Journal on Advanced Science, Education, and Religion, 2025)
The aim of this research is to assess how well class III science students at MI Munada Sungai Nibung learn when using audio-visual based learning resources. The background to this research is the lack of use of technology in the classroom, which contributes to poor learning outcomes for students. This research methodology is quantitative and uses a pretest-posttest control group design, which is a real experimental design. Two groups formed the sample: a control group, which used traditional techniques, and an experimental group, which received treatment using audio-visual media. According to the findings, the average pretest score of the experimental class was 64.2, while the control group was 63.8. After therapy, the experimental class's average posttest score rose to 81.6, compared to 72.4 for the control group. There is a substantial difference in the learning outcomes of students using audio-visual media and traditional techniques, according to the t-test, which revealed a significance value of 0.000 <0.05. This study shows how the use of audio-visual materials can improve students' understanding of the subject matter, increase their motivation to learn, and encourage more interaction between them during class. The success of implementing learning media is also influenced by the availability of infrastructure and facilities, as well as instructors' readiness to use technology, according to this study. The implications of this research emphasize the importance of developing technology-based learning media in improving the quality of learning and student learning outcomes. Therefore, the use of audio-visual media is recommended as an effective strategy for increasing students' conceptual understanding and absorption in science learning.